ANALISA PUTUSAN PENGADILAN TERKAIT PENGHAPUSAN MEREK YANG TIDAK DIGUNAKAN MENURUT UNDANG-UNDANG NOMOR 15 TAHUN 2001 TENTANG MEREK - Centaury, Patricia Irinne Alpha (JURNAL MEDIA HUKUM DAN PERADILAN, 2018)
Based on the provisions of Article 61 paragraph (2) letter (a) of Law No. 15 of 2001 explains that the brand can be removed from the list of the brands if the brand is not used for three (3) consecutive years from the date of the last registration. One of the problems arise when the brand